PORPHYRY COPPER DEPOSITS OF THE CIS AND THE MODELS OF THEIR FORMATION - Zvezdov V.S.; Migachev I.F.; Girfanov M.M. (My University, 1993)
Deposits of the “porphyry” family (essentially porphyry copper and gold-porphyry copper, gold-bearing porphyry molybdenum-copper, gold-containing porphyry copper-molybdenum and porphyry molybdenum deposits) are associated in time and space with granitoid magmatism mainly in Phaerozoic volcano-plutonic belts. Whatever their age, the deposits belong to two types of belts: basaltic belts, representing axial zones of island arcs, or andesitic belts formed within active continental (Andean-type) margins.